PENDUGAAN PRODUKSI BIOMASSA HIJAUAN RUMPUT Brachiaria decumbens BERDASARKAN METODE NON-DESTRUKTIF DENGAN MENGGUNAKAN PIRINGAN AKRILIK - Suryanah, Sari; Dudi, -; Mansyur, - (Pastura, 2014)
The aims of this research was to know the relation between forage height and its dry matter yield and also the relation between forage depressed height and its dry matter yield. The research method used was non-destructive method by using acrylic plate in a Brachiaria decumbens grass aged 40 days at area 1500 m2. The results of this research indicatedthat forage height has a low influence to its dry matter yield (R2=0,13-0,30)and forage depressed height also has a low influence to dry matter yield of Brachiaria decumbens (R2=0,20-0,37).
Keywords: Brachiaria decumbens grass, non-destructive method, acrylicplate, regression equation